Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

First, we need to factor the expression [tex]\(2x^2 + 7x + 6\)[/tex].

[tex]\[
\begin{array}{l}
2x^2 + 7x + 6 \\
2x^2 + 3x + 4x + 6 \\
\left(2x^2 + 3x\right) + \left(4x + 6\right) \\
x(2x + 3) + 2(2x + 3) \\
(x + 2)(2x + 3)
\end{array}
\][/tex]

So, [tex]\(2x^2 + 7x + 6 = (x + 2)(2x + 3)\)[/tex]. Therefore, we can rewrite our original equation as:
[tex]\[
(x + 2)(2x + 3) = 0
\][/tex]

Now we can use the zero product property to solve for [tex]\(x\)[/tex].

[tex]\[
\begin{array}{l}
2x + 3 = 0 \\
2x = -3 \\
x = -\frac{3}{2}
\end{array}
\][/tex]

OR

[tex]\[
\begin{array}{c}
x + 2 = 0 \\
x = -2
\end{array}
\][/tex]


Sagot :

Certainly! Let's go through the complete solution step-by-step.

We need to factor the quadratic equation [tex]\(2x^2 + 7x + 6 = 0\)[/tex].

1. First, identify the quadratic expression: [tex]\(2x^2 + 7x + 6\)[/tex].

2. To factor it, we look for two numbers that multiply to the product of the coefficient of [tex]\(x^2\)[/tex] (which is 2) and the constant term (which is 6). These numbers must also add up to the coefficient of [tex]\(x\)[/tex] (which is 7).

- The product of 2 (coefficient of [tex]\(x^2\)[/tex]) and 6 (constant term) is [tex]\(2 \times 6 = 12\)[/tex].
- We need two numbers that multiply to 12 and add up to 7. These numbers are 3 and 4.

3. Rewrite the middle term using these two numbers:
[tex]\[ 2x^2 + 7x + 6 = 2x^2 + 3x + 4x + 6 \][/tex]

4. Group the terms:
[tex]\[ (2x^2 + 3x) + (4x + 6) \][/tex]

5. Factor by grouping:
[tex]\[ x(2x + 3) + 2(2x + 3) \][/tex]

6. Notice that [tex]\(2x + 3\)[/tex] is a common factor:
[tex]\[ (x + 2)(2x + 3) \][/tex]

So, we have factored [tex]\(2x^2 + 7x + 6\)[/tex] as [tex]\((x + 2)(2x + 3)\)[/tex].

Now, solve the factored equation [tex]\((x + 2)(2x + 3) = 0\)[/tex] using the zero product property:

7. Set each factor to zero:
[tex]\[ x + 2 = 0 \quad \text{or} \quad 2x + 3 = 0 \][/tex]

8. Solve each equation for [tex]\(x\)[/tex]:

For [tex]\(x + 2 = 0\)[/tex]:
[tex]\[ x = -2 \][/tex]

For [tex]\(2x + 3 = 0\)[/tex]:
[tex]\[ 2x = -3 \implies x = -\frac{3}{2} \implies x = -1.5 \][/tex]

Therefore, the solutions to the quadratic equation [tex]\(2x^2 + 7x + 6 = 0\)[/tex] are:
[tex]\[ x = -2 \quad \text{and} \quad x = -1.5 \][/tex]

These are the roots of the quadratic equation.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.